1983
DOI: 10.1177/0146167283092003
|View full text |Cite
|
Sign up to set email alerts
|

The False Consensus Effect in Estimates of Smoking Prevalence

Abstract: The current study investigated four possible causal mechanisms underlying the false consensus effect in the context of cigarette smoking. Little support was found for attributional or conformity-based mechanisms. However, support for both a selective exposure and a motivational explanation was found.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
144
0
1

Year Published

1995
1995
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(153 citation statements)
references
References 7 publications
8
144
0
1
Order By: Relevance
“…Such findings suggest that a fourth potential source of the false-consensus effect may stem from motivational processes that are not "cognitive," but that instead take place automatically when an individual experiences an emotional need for social self-enhancement or personal self-esteem maintenance (Marks and Miller, 1987). Of particular relevance, for example, research finds significant false-consensus effects when respondents are asked to estimate the prevalence of behaviors/attitudes that they hold but that are not universally approved (e.g., Sherman et al, 1984) and these results are stronger among adolescent respondents than among adult respondents (e.g., Sherman et al, 1983). Thus, some evidence suggests that false-consensus may serve as an automatic, emotional means by which the adolescent psyche essentially "normalizes" delinquency.…”
Section: Perceptual Bias Among Measures Of Perceived Peer Delinquencymentioning
confidence: 99%
See 1 more Smart Citation
“…Such findings suggest that a fourth potential source of the false-consensus effect may stem from motivational processes that are not "cognitive," but that instead take place automatically when an individual experiences an emotional need for social self-enhancement or personal self-esteem maintenance (Marks and Miller, 1987). Of particular relevance, for example, research finds significant false-consensus effects when respondents are asked to estimate the prevalence of behaviors/attitudes that they hold but that are not universally approved (e.g., Sherman et al, 1984) and these results are stronger among adolescent respondents than among adult respondents (e.g., Sherman et al, 1983). Thus, some evidence suggests that false-consensus may serve as an automatic, emotional means by which the adolescent psyche essentially "normalizes" delinquency.…”
Section: Perceptual Bias Among Measures Of Perceived Peer Delinquencymentioning
confidence: 99%
“…Most of this research is focused on health risk behaviors with a number of studies finding evidence of robust false-consensus effects for such behaviors such as substance use (e.g. Iannotti and Bush, 1992;Kandel, 1980;Sherman et al, 1983;Urberg et al,1990;Wolfson, 2000) and only preliminary evidence finding somewhat weaker falseconsensus effects for serious forms of delinquency like violence (Prinstein and Wang, 2005).…”
Section: Implications For Understanding and Controlling Juvenile Crimmentioning
confidence: 99%
“…As a result, people overestimate the level of consensus that exists for their own position in the population as a whole because such judgements are based on the restricted or biased sample to which they are selectively exposed. For example, Sherman et al (1983) showed that people's estimate of smoking prevalence was smaller for those who associated mainly with non-smokers than for those who associated mainly with smokers. The ® ndings of several other studies that have investigated social projection tendencies within the context of in-groups and out-groups (Holtz and Miller 1985) are also consistent with this explanation.…”
Section: False Consensusmentioning
confidence: 99%
“…The ® ndings of several other studies that have investigated social projection tendencies within the context of in-groups and out-groups (Holtz and Miller 1985) are also consistent with this explanation. Moreover, a number of key researchers in the ® eld (Ross et al 1977, Sherman et al 1983, Marks and Miller 1987 have suggested that selective exposure is the primary factor generating the FCE. However, since exposure has never been directly manipulated, its eVect on cognitive availability and its more proximate eVect on consensus estimates remains inconclusive.…”
Section: False Consensusmentioning
confidence: 99%
“…Specific theories in health behavior research that have been employed to explain these phenomena that increase one's sense of certainty include the false consensus effect (Sherman, et al 1983), illusory correlation (McConnell, Sherman, & Hamilton, 1994), implicit cognition theory (Stacy & Ames, 2001), and unrealistic optimism (Weinstein, 1982;Weinstein, 1987). The false consensus effect refers to a tendency to believe that one's own attitudes or behaviors are more prevalent than they actually are.…”
Section: Cognition-information Errorsmentioning
confidence: 99%